Key Ingredients in the Search for Social Justice: A Case Study of Best Practices in a Calcutta School - Jessop, Tansy S. (Catholic Education: A Journal of Inquiry and Practice, 2001)
This article examines the key ingredients in a Catholic inner-city school that have contributed to a paradigm shift in the school community. The school has relinquished a comfortable niche educating children of Calcutta’s elite in favor of the messy and risky business of engaging with the poor. It has asserted the right of every child to quality education, dared to cross social boundaries, and succeeded in integrating a widely disparate parent and child community. The article elaborates on a cluster of key ingredients which together constitute a pathway for transforming schools into those which practice social justice and provide quality education. It examines widely recognized change principles in action within a particular setting and relates that the achievement of equity and excellence are not mutually exclusive. It explores the distinctive values, ethos, teaching and learning strategies, leadership, staff and culture of the school that promote learning despite flouting conventional selection and social class norms, in order to distill the key ingredients which make for excellence and equity. This essay begins by setting the study in context, describes the research methodology briefly, and then provides an analysis of a model of best practice and a pathway to social transformation that the school has adopted.